2020
DOI: 10.3390/s20226543
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design and Crawling Pattern Generator of a Planar Quadruped Robot for High-Payload Locomotion

Abstract: Load capacity is an important index to reflect the practicability of legged robots. Existing research into quadruped robots has not analyzed their load performance in terms of their structural design and control method from a systematic point of view. This paper proposes a structural design method and crawling pattern generator for a planar quadruped robot that can realize high-payload locomotion. First, the functions required to evaluate the leg’s load capacity are established, and quantitative comparative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The details of the structure comparison and jumping simulation results are shown in Figures 3 and 4. More comparative analyses of parallel and serial structure of legged robot are presented in another paper [26]. Previous research has shown that the ideal mass ratio of the leg involves a large trunk mass and a lower leg mass [27].…”
Section: Robotic System Designmentioning
confidence: 99%
“…The details of the structure comparison and jumping simulation results are shown in Figures 3 and 4. More comparative analyses of parallel and serial structure of legged robot are presented in another paper [26]. Previous research has shown that the ideal mass ratio of the leg involves a large trunk mass and a lower leg mass [27].…”
Section: Robotic System Designmentioning
confidence: 99%
“…The design of the spike tires (Figure 2) was proposed with four spike elements (9), which consist of a support rod (1) and two spikes (2). Each element is placed in the tire groove (6) made in the tire tread pattern.…”
Section: Design Of Driving Wheelsmentioning
confidence: 99%
“…The drawbar pulls of the test tractor with standard tires, spike tires, and blade wheels with low and high loads are shown in Figure 6. The RMS drawbar pull values of the tractor with different driving wheels with low and high loads, calculated according to Equation (2), are presented in Table 2. The levels of the drawbar RMS values are shown as straight lines in Figure 5.…”
Section: Evaluation Of Drawbar Pull Frequency Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the automatic development of such cooperative tasks requires the use of human compatible devices in order to avoid collisions or actions that can harm people, mainly using laser range sensors [ 1 , 2 ], depth cameras [ 3 , 4 ], or surveillance systems [ 5 ]. On the other hand, the automatic development of cooperative tasks requires the use of human compatible devices moving like people in common spaces designed for people, mainly using legs [ 6 ], omnidirectional wheels [ 7 ], or hybrid legs [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%